Membrane unit, preparation method thereof, battery cell and all-solid-state lithium ion battery

By using a diaphragm unit with a composite electrolyte diaphragm structure including a first electrolyte layer, a porous support layer and a second electrolyte layer in an all-solid state lithium-ion battery, the problem that diaphragm units in the prior art is difficult to take into account high mechanical and high electrical performance, and the high efficiency and long life of the battery are achieved.

CN119764538APending Publication Date: 2025-04-04GUOLIAN CORE MATERIALS (BEIJING) TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510011332.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The diaphragm units of existing all-solid-state lithium-ion batteries are difficult to take into account both high mechanical and electrical properties, which makes it difficult to achieve battery assembly reliability and energy density design requirements.

Method used

The diaphragm unit structure includes a negative electrode diaphragm, a composite electrolyte diaphragm and a positive electrode diaphragm. The composite electrolyte diaphragm consists of a first electrolyte layer, a porous support layer and a second electrolyte layer. The first electrolyte layer comes in contact with the negative electrode diaphragm, and the second electrolyte layer comes in contact with the positive electrode diaphragm. By precisely controlling the thickness ratio of the electrolyte layer and the structure of the porous support layer, the mechanical and electrochemical properties of the diaphragm unit are improved.

Benefits of technology

It significantly improves the electrochemical performance and cyclic stability of the battery, enhances the shear strength and ion conduction ability of the diaphragm unit, solves the micro-short circuit problem in battery assembly, and improves the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764538A_ABST
    Figure CN119764538A_ABST
Patent Text Reader

Abstract

The invention provides a diaphragm unit, a preparation method thereof, a battery cell and an all-solid-state lithium ion battery. The membrane unit comprises a negative electrode membrane, a composite electrolyte membrane and a positive electrode membrane which are sequentially stacked; the composite electrolyte membrane comprises a first electrolyte layer, a porous supporting layer and a second electrolyte layer which are sequentially stacked, the first electrolyte layer is in contact with the negative electrode membrane, and the second electrolyte layer is in contact with the positive electrode membrane; the porous supporting layer, the first electrolyte layer and the second electrolyte layer all comprise electrolyte; and the thickness ratio of the first electrolyte layer to the second electrolyte layer is (1.5-6.0): 1. The invention designs a composite electrolyte membrane structure comprising two electrolyte layers and a middle porous support layer, and through the cooperation of the composite electrolyte membrane structure with the positive electrode membrane and the negative electrode membrane, the electrochemical performance and the cycle stability of the battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a diaphragm unit, a preparation method thereof, a battery cell and an all-solid-state lithium-ion battery. Background Art

[0002] Energy storage systems continue to develop in the direction of high specific energy and high safety. All-solid-state secondary batteries that use solid electrolytes instead of organic electrolytes and separators are regarded as one of the most promising next-generation energy storage technologies due to their inherent high safety and high energy density. The electrical properties, mechanical properties and thickness of the electrolyte membrane are the fundamental factors that determine the performance of all-solid-state batteries.

[0003] For the assembly of multi-layer solid-state batteries, one side of the electrolyte membrane is a relatively soft graphite, silicon-based, lithium metal negative electrode, and the other side is a relatively hard lithium iron phosphate, ternary positive electrode that is slightly smaller than the negative electrode. When external pressure is applied after the battery cell is assembled, the positive electrode is prone to damage the electrolyte membrane due to insufficient shear strength, which eventually leads to a micro short circuit in the battery and makes it unable to work. Therefore, a high-strength electrolyte membrane is required to improve the reliability of battery assembly.

[0004] CN114207887B discloses a non-woven electrolyte membrane, which melts the resin while mixing it through an extruder. The non-woven fabric manufacturing machine forms the resin into a fiber shape to form a non-woven fabric, and then applies a slurry containing solid electrolyte particles to the non-woven fabric, and dries and pressurizes it to form a solid electrolyte membrane. This method uses conventional electrolytes for coating and film formation, which is not conducive to ultra-thin electrolyte membranes, and the assembly shear resistance is limited, and it cannot solve the design requirements of battery micro-short circuits and energy density. CN117558976B discloses an electrolyte membrane, including a conductive polymer material, an inorganic filler material and a lithium salt. The full concentration gradient composite solid electrolyte membrane has a relative first surface and a second surface, and the concentration of the conductive polymer material is distributed in an increasing manner from the first surface to the second surface, and the concentration of the inorganic filler material is distributed in an increasing manner from the second surface to the first surface, which can alleviate the agglomeration of the non-polar filler and thus improve the ionic conductivity of the electrolyte membrane. This method has little design consideration for the mechanical performance requirements of the electrolyte membrane, and it is difficult to meet the requirements of engineering preparation of back-end battery assembly.

[0005] CN117577930A discloses an electrolyte membrane, which is formed by rolling after mixing solid electrolyte, adhesive and additive, heating to degas, and hot pressing to set. This method can prepare electrolyte membrane, but the mechanical strength is relatively low, and the back-end battery assembly process and equipment are high. Although the manufacturing cost of electrolyte membrane is not high, the battery assembly cost is high. CN117832596A discloses a method for preparing electrolyte membrane, which is to mix solvent, adhesive and sulfide electrolyte, and to coat, vibrate, dry and pressurize the electrolyte slurry obtained after mixing, so that the electrolyte particles inside the solid electrolyte membrane are more densely packed, and the overall mechanical and electrochemical properties are better. At the same time, due to the close packing between particles, the proportion of adhesive required for the membrane is reduced, which further improves the electrochemical properties of the electrolyte membrane. The design of the mechanical properties of the electrolyte membrane is not considered enough, and the mechanical strength of the electrolyte and adhesive directly forming the film is difficult to meet the requirements of engineering design.

[0006] The current existing technology has alleviated the problem of electrolyte membrane ion transport to a certain extent, but the battery assembly difficulty in actual engineering design is relatively high. The design of high-energy-density batteries has higher requirements on the weight ratio and thickness of the electrolyte membrane. The existing electrolyte membrane technology still has a lot of room for improvement.

[0007] Based on this, how to provide a membrane unit for an all-solid-state battery and its corresponding preparation method so that the obtained membrane unit has higher electrochemical properties and mechanical strength, thereby effectively improving the electrical performance of the final all-solid-state battery, is one of the important technical problems that need to be solved in this field. Summary of the invention

[0008] The main purpose of the present invention is to provide a diaphragm unit, a preparation method thereof, a battery cell and an all-solid-state lithium-ion battery to solve the problem that the diaphragm unit of the all-solid-state lithium-ion battery in the prior art is difficult to achieve both high mechanical properties and electrical properties.

[0009] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a diaphragm unit, which includes a negative electrode diaphragm, a composite electrolyte diaphragm and a positive electrode diaphragm stacked in sequence; the composite electrolyte diaphragm includes a first electrolyte layer, a porous support layer and a second electrolyte layer stacked in sequence, the first electrolyte layer is arranged in contact with the negative electrode diaphragm, and the second electrolyte layer is arranged in contact with the positive electrode diaphragm; the porous support layer, the first electrolyte layer and the second electrolyte layer all include electrolytes; and the thickness ratio of the first electrolyte layer to the second electrolyte layer is (1.5~6.0):1.

[0010] Furthermore, the thickness of the porous support layer is 5 μm to 30 μm; the porous support layer also includes a membrane skeleton material, and the median pore size of the membrane skeleton material is 600 nm to 1000 nm; the membrane skeleton material is selected from one or more of non-woven fabrics, cellulose membranes and inorganic aerogel membranes.

[0011] Furthermore, the first electrolyte layer includes a first electrolyte, the second electrolyte layer and the porous support layer both include a second electrolyte, and: the ratio of D50 of the first electrolyte to the median value of the pore size is 5 to 15; the D50 of the second electrolyte is less than the median value of the pore size; and the content of the second electrolyte is 50% to 98% based on the total weight of the porous support layer as 100%.

[0012] Furthermore, the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is (2-20):1.

[0013] Furthermore, the first electrolyte and the second electrolyte are each independently selected from one or more of a sulfide electrolyte, a halide electrolyte, a halide oxide electrolyte, a lithium aluminum titanium phosphate electrolyte, a lithium aluminum germanium phosphate electrolyte, a lithium lanthanum zirconium oxide electrolyte, a lithium lanthanum titanium oxide electrolyte and an organic / inorganic composite electrolyte; the organic / inorganic composite electrolyte is a poly(propylene carbonate)-coated sulfide electrolyte, the poly(propylene carbonate)-coated sulfide electrolyte comprises a poly(propylene carbonate) coating layer and a sulfide electrolyte core, and the weight ratio of the poly(propylene carbonate) coating layer to the sulfide electrolyte core is (0.05-1):100.

[0014] The second aspect of the present invention provides a method for preparing the above-mentioned diaphragm unit, comprising: step S1, providing a membrane skeleton material, the membrane skeleton material having a first surface and a second surface arranged opposite to each other; step S2, preparing a first electrolyte and a second electrolyte into a slurry, and applying the slurry on the first surface of the membrane skeleton material, so that the second electrolyte in the slurry passes through the first surface and infiltrates the membrane skeleton material to form a second electrolyte layer and a porous support layer; the first electrolyte forms a first electrolyte layer on the first surface, thereby obtaining a composite electrolyte membrane; or, preparing the first electrolyte into a first slurry, and applying the first slurry on the first surface of the membrane skeleton material to form a first electrolyte layer; preparing the second electrolyte into a second slurry, and applying the second slurry on the second surface of the membrane skeleton material, so that the second slurry infiltrates the membrane skeleton material to form a second electrolyte layer and a porous support layer, thereby obtaining a composite electrolyte membrane; step S3, preparing the negative electrode active material into a negative electrode membrane; preparing the positive electrode active material into a positive electrode membrane; step S4, bonding the negative electrode membrane to the first electrolyte layer, and bonding the positive electrode membrane to the second electrolyte layer, thereby obtaining a diaphragm unit.

[0015] Furthermore, in the slurry, the weight ratio of the first electrolyte to the second electrolyte is (3-4):1.

[0016] Furthermore, the solid contents of the slurry, the first slurry and the second slurry are each independently 20 wt % to 75 wt %.

[0017] A third aspect of the present invention provides a battery cell, comprising a positive electrode current collector, a negative electrode current collector and a diaphragm unit, wherein the diaphragm unit is the diaphragm unit described above.

[0018] A fourth aspect of the present invention provides an all-solid-state lithium-ion battery, comprising the above-mentioned battery cell.

[0019] By applying the technical solution of the present invention, a composite electrolyte membrane structure including two electrolyte layers and an intermediate porous support layer is designed. In particular, the thickness ratio of the first electrolyte layer to the second electrolyte layer is precisely controlled, and through its coordination with the positive electrode membrane and the negative electrode membrane, the electrochemical performance and cycle stability of the battery are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0021] Figure 1 Schematic diagram of the structure of the diaphragm unit in this application.

[0022] The above drawings include the following reference numerals:

[0023] 10. Negative electrode membrane; 20. Composite electrolyte membrane; 21. First electrolyte layer; 22. Porous support layer; 23. Second electrolyte layer; 30. Porous electrode membrane. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0025] As described in the background art, the diaphragm unit of the all-solid-state lithium-ion battery in the prior art has the problem of being difficult to balance high mechanical properties and electrical properties. In order to solve the above technical problems, the first aspect of the present invention provides a diaphragm unit, such as Figure 1As shown, the membrane unit includes a negative electrode membrane 10, a composite electrolyte membrane 20 and a positive electrode membrane 30 stacked in sequence; the composite electrolyte membrane 20 includes a first electrolyte layer 21, a porous support layer 22 and a second electrolyte layer 23 stacked in sequence, the first electrolyte layer 21 is arranged in contact with the negative electrode membrane 10, and the second electrolyte layer 23 is arranged in contact with the positive electrode membrane 30; the porous support layer 22, the first electrolyte layer 21 and the second electrolyte layer 23 all include electrolytes; and the thickness ratio of the first electrolyte layer 21 to the second electrolyte layer 23 is (1.5~6.0):1.

[0026] The membrane unit structure provided by the present invention includes a special composite electrolyte membrane 20, which includes a first electrolyte layer 21, a second electrolyte layer 23 and a porous support layer 22 interspersed between the two electrolyte layers. When the composite electrolyte membrane structure is compounded with the positive electrode membrane structure and the negative electrode membrane structure in the manner that the first electrolyte layer 21 is arranged in contact with the negative electrode membrane 10, and the second electrolyte layer 23 is arranged in contact with the positive electrode membrane 30, the resulting membrane unit can simultaneously exhibit high mechanical properties and electrical properties.

[0027] Specifically, in practical applications, the positive electrode produces a shearing effect on the composite electrolyte membrane of the obtained membrane unit, and at this time, the thicker first electrolyte layer 21 and the thinner second electrolyte layer 23 can cooperate as a whole to protect the overall structural integrity of the composite electrolyte membrane 20 and prevent it from being damaged. At the same time, it cannot be ignored that the composite electrolyte membrane 20 is interspersed with a porous support layer 22, and the porous support layer 22 also contains an electrolyte, which can serve as a reinforcing skeleton to support the composite electrolyte membrane and promote ion conduction, so that it has both excellent electrical properties and excellent mechanical strength.

[0028] In particular, the present invention precisely controls the thickness ratio of the first electrolyte layer 21 to the second electrolyte layer 23 to be (1.5-6.0):1. This thickness relationship obtained through a large number of experiments can significantly balance the ion conductivity and mechanical strength of the resulting membrane unit, thereby improving the energy density of the corresponding battery cell while ensuring the typical safety and long cycle life of the battery.

[0029] In order to enhance the mechanical strength of the obtained membrane unit and optimize the ion conduction channel therein, the thickness of the porous support layer 22 is preferably 5 μm to 30 μm.

[0030] Furthermore, the porous support layer 22 also includes a membrane skeleton material, and the electrolyte is dispersed on the membrane skeleton material, and the median value of the pore size of the membrane skeleton material is 600nm to 1000nm. The membrane skeleton material having the above-mentioned specific pore size structure is arranged in the porous support layer 22, which can significantly optimize the electrolyte distribution therein, and reduce the overheating phenomenon caused by uneven heat transfer during the application of the obtained diaphragm unit, thereby effectively improving the service life of the obtained diaphragm unit. In several preferred embodiments, the membrane skeleton material is selected from one or more of non-woven fabrics, cellulose membranes and inorganic aerogel membranes. The selection of these several membrane skeleton materials not only improves the processability and compatibility of the diaphragm unit, but also can better cooperate with the electrolyte dispersed thereon, thereby synergistically improving the mechanical properties and electrical properties of the obtained diaphragm unit. Among them, the inorganic aerogel membrane can be specifically one of a silica aerogel membrane, an alumina aerogel membrane and a titanium dioxide aerogel membrane.

[0031] In several preferred embodiments, the inventors have conducted a large number of experiments and preferably the first electrolyte layer 21 includes the first electrolyte, the second electrolyte layer 23 and the porous support layer 22 both include the second electrolyte, and: the ratio of the D50 of the first electrolyte to the median value of the pore size is 5 to 15; the D50 of the second electrolyte is less than the median value of the pore size. In other words, with respect to the pore size of the above-mentioned membrane skeleton material, the present invention has strictly optimized the electrolyte particle size in the electrolyte layers on both sides thereof, and found that the coordinated control of the above-mentioned pore size and particle size can more significantly improve the good wettability of the second electrolyte and the membrane skeleton material, and improve the comprehensive performance of the resulting composite membrane. And more importantly, this relationship between particle size and pore size enables the first electrolyte layer containing a large-particle first electrolyte to better play a rigid support role, the second electrolyte layer containing a small-particle second electrolyte to better play a toughness role, and the middle porous support layer to better play a skeleton role. The three work together to form an overall force-bearing structure similar to reinforced concrete, and ultimately significantly inhibit the phenomenon of electrolyte membrane damage caused by positive electrode shear, so that the resulting membrane unit has higher shear strength and electrochemical properties.

[0032] Furthermore, the content of the second electrolyte is 50% to 98% based on the total weight of the porous support layer 22 being 100%. Optimizing the content of the second electrolyte in the porous support layer 22 as above can more effectively balance the electrochemical properties and mechanical properties of the porous support layer 22 and the resulting membrane unit, thereby enabling the corresponding battery cell to have better comprehensive electrical properties.

[0033] In order to further improve the ion conductivity and shear strength of the composite electrolyte membrane, the ratio of the thickness of the first electrolyte layer 21 to the D50 of the first electrolyte is preferably (2-20): 1, preferably (2.5-3.0): 1. In addition, in order to coordinate the thickness and mechanical properties of each membrane, the thickness of the negative electrode membrane 10 and the positive electrode membrane 30 is preferably 70 μm to 80 μm, respectively, so as to further improve the shear strength of the obtained membrane unit.

[0034] In several preferred embodiments, the first electrolyte and the second electrolyte are independently selected from one or more of a sulfide electrolyte, a halide electrolyte, an oxyhalide electrolyte, a lithium aluminum titanium phosphate electrolyte, a lithium aluminum germanium phosphate electrolyte, a lithium lanthanum zirconium oxide electrolyte, a lithium lanthanum titanium oxide electrolyte, and an organic / inorganic composite electrolyte. The selection of the above electrolytes, compared with the types of electrolytes commonly used in the art, can better infiltrate the membrane skeleton material, thereby more effectively reducing the short circuit risk of the final all-solid-state lithium-ion battery. In several more preferred embodiments, the organic / inorganic composite electrolyte is a poly(propylene carbonate)-coated sulfide electrolyte, and the poly(propylene carbonate)-coated sulfide electrolyte includes a poly(propylene carbonate) coating layer and a sulfide electrolyte core, and the weight ratio of the poly(propylene carbonate) coating layer to the sulfide electrolyte core is (0.05-1):100. The inventors have preferred the specific types of organic / inorganic composite electrolytes as above, and found that the poly(propylene carbonate)-coated sulfide electrolyte with the above characteristics can be better adapted to the above composite system to obtain a membrane unit with higher comprehensive performance, and its corresponding battery cell exhibits more excellent electrical performance and storage performance.

[0035] The second aspect of the present invention provides a method for preparing the above-mentioned membrane unit, comprising: step S1, providing a membrane skeleton material, the membrane skeleton material having a first surface and a second surface arranged opposite to each other; step S2, preparing a first electrolyte and a second electrolyte into a slurry, and applying the slurry on the first surface of the membrane skeleton material, so that the second electrolyte in the slurry penetrates the first surface and infiltrates the membrane skeleton material to form a second electrolyte layer 23 and a porous support layer 22; the first electrolyte forms a first electrolyte layer 21 on the first surface, thereby obtaining a composite electrolyte membrane 20; or, preparing the first electrolyte into a first slurry, and The first slurry is applied on the first surface of the membrane skeleton material to form a first electrolyte layer 21; the second electrolyte is prepared into a second slurry, and the second slurry is applied on the second surface of the membrane skeleton material so that the second slurry infiltrates the membrane skeleton material to form a second electrolyte layer 23 and a porous support layer 22, thereby obtaining a composite electrolyte membrane 20; step S3, the negative electrode active material is prepared into a negative electrode membrane 10; the positive electrode active material is prepared into a positive electrode membrane 30; step S4, the negative electrode membrane 10 is bonded to the first electrolyte layer 21, and the positive electrode membrane 30 is bonded to the second electrolyte layer 23 to obtain a membrane unit.

[0036] With respect to the above-mentioned diaphragm unit, the present invention provides a corresponding preparation method, which realizes high-precision interlayer matching in the diaphragm unit through a precise and simple process, significantly improves its manufacturing yield and consistency, reduces production costs, and is conducive to the commercialization and industrialization of its corresponding battery cells and all-solid-state lithium-ion batteries.

[0037] Among them, for the steps of forming the first electrolyte layer, the second electrolyte layer and the porous support layer, the present invention provides two methods. One is to first apply the first electrolyte with a large particle size into a layer, and then apply and infiltrate the second electrolyte with a small particle size to obtain the second electrolyte layer and the porous support layer, that is, to prepare the composite electrolyte membrane through a two-step method.

[0038] The other method is to directly prepare two electrolytes of different particle sizes into a uniform slurry, and then use the relationship between the two and the pore size of the membrane skeleton material to make the first electrolyte with a larger particle size unable to pass through the membrane skeleton material, and directly form a first electrolyte layer on the first surface to which it is applied, and the second electrolyte with a smaller particle size mostly passes through the first surface and the membrane skeleton material to form a second electrolyte layer on its second surface, while the small part of the second electrolyte that passes through the first surface is retained in the membrane skeleton material and evenly dispersed therein, forming a porous support layer together with the membrane skeleton material. That is, a complete composite electrolyte membrane is directly formed in one step. This preparation process cleverly uses the relationship between particle size and pore size, and more easily realizes the preparation of composite electrolyte membranes. It is more suitable for engineering preparation, has higher compatibility with existing battery manufacturing equipment, and has more practical application value.

[0039] It should be noted that when the composite membrane is prepared by the one-step method, in actual production, it is inevitable that a small portion of the second electrolyte fails to penetrate the membrane skeleton material to form the second electrolyte layer, but remains in the first electrolyte layer. Therefore, the portion is very small compared to the total amount of the second electrolyte and will not affect the performance of the final membrane unit or battery cell. Therefore, in the present invention, all the second electrolyte is considered to be present in the second electrolyte layer or the porous support layer.

[0040] Furthermore, in the process of forming the electrolyte layer provided by the present invention, for the first electrolyte layer 21 and the second electrolyte layer 23, the one-step method and the two-step method are used by default, and the same coating thickness, coating surface density, drying conditions and rolling conditions are used to densify them. On this basis, the difference in thickness between the first electrolyte layer 21 and the second electrolyte layer 23 is mainly related to the particle size and weight of the electrolyte therein.

[0041] In several typical embodiments, the weight ratio of the first electrolyte to the second electrolyte in the slurry is (3-4): 1. That is, when the one-step method is used for preparation, the weight relationship of the two electrolytes is preferably as above, which can better adapt to the preparation process conditions and more effectively utilize the difference in the particle size range of the two electrolytes, thereby preparing a membrane unit with high shear strength and electrochemical performance.

[0042] Furthermore, the solid content of the slurry, the first slurry and the second slurry is independently 20wt% to 75wt%. The solid content of the slurry involved in the preparation process is preferably as above, which can effectively optimize the coating process, improve the density and stability of the obtained two electrolyte layers, and thus improve the discharge stability and service life of the corresponding battery cell.

[0043] The third aspect of the present invention provides a battery cell, comprising a positive electrode current collector, a negative electrode current collector and a membrane unit, wherein the membrane unit is the above-mentioned membrane unit. The membrane unit obtained by the present invention has high shear strength and high electrochemical performance, so when it is further applied to a battery cell, the obtained battery cell has a higher capacity and a more stable discharge curve.

[0044] The fourth aspect of the present invention provides an all-solid-state lithium-ion battery, which includes the above-mentioned battery cell. The above-mentioned battery cell obtained by the present invention has better electrochemical performance. When further assembled with components such as a housing, a protection circuit and a connector to form an all-solid-state lithium-ion battery, it can effectively solve the problem of assembly micro-short circuits and potential micro-short circuits of lithium-ion solid-state batteries causing high self-discharge of the battery, thereby significantly improving its capacity and charge and discharge stability.

[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0046] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0047] Example 1

[0048] A method for preparing a diaphragm unit:

[0049] Step S1, providing a non-woven fabric with a thickness of 15 μm as a membrane skeleton material of a porous support layer, wherein the median value of the pore size is 600 nm through scanning electron microscopy combined with image statistical analysis.

[0050] Step S2, select a sulfide (Li6PS5Cl) electrolyte with a D50 of 5 μm as the first electrolyte, select a sulfide (Li6PS5Cl) electrolyte with a D50 of 500 nm as the second electrolyte (wherein the ratio of the D50 of the first electrolyte to the median pore size of the porous support is 8.33), mix them in a weight ratio of first electrolyte: second electrolyte = 4:1, and add a binder nitrile butadiene rubber accounting for 2% of the total weight of the first electrolyte and the second electrolyte, and then use p-xylene as a dispersing solvent to obtain a suspension slurry with a solid content of 65wt%.

[0051] The slurry is coated on the upper surface of the membrane skeleton material. At this time, most of the second electrolyte with D50 < 600nm in the slurry passes through the membrane skeleton material to reach the lower surface, and forms a second electrolyte layer on the lower surface after drying. A small part remains in the microporous structure of the non-woven membrane skeleton material and forms a porous support layer together with the non-woven fabric (the total weight of the porous support layer obtained after drying is 100%, of which the content of the second electrolyte is 95%); while the first electrolyte cannot pass through the membrane skeleton material due to its large particle size, and forms a first electrolyte layer on its upper surface after drying. After rolling and densification, a composite electrolyte membrane with a total thickness of 35μm is obtained, wherein the thickness of the porous support layer is 15μm, and the thickness ratio of the first electrolyte layer to the second electrolyte layer is 70:30. At this time, the thickness of the first electrolyte layer is 14μm, and the ratio of its D50 to the first electrolyte is 2.8:1.

[0052] Step S3: Using the ternary positive electrode material nickel cobalt manganese oxide lithium 811 as the positive electrode active material, and mixing it with polytetrafluoroethylene, carbon nanotubes, and sulfide electrolyte in a weight ratio of 82:2:1:15, and mixing it in a ratio of 3.5 mAh / cm 2The film was formed and dried to obtain a positive electrode film with a thickness of 80 μm. The silicon-based composite negative electrode material silicon oxygen carbon was used as the negative electrode active material, and it was mixed with styrene butadiene rubber, carbon nanotubes, and sulfide electrolyte in a weight ratio of 75:10:1:14, and the surface capacity was 3.85 mAh / cm 2 The film was formed and dried to obtain a negative electrode film with a thickness of 75 μm.

[0053] Step S4, the thicker side of the electrolyte layer in the composite electrolyte membrane, i.e., the first electrolyte layer, is attached to the positive electrode, and the thinner side of the electrolyte layer, i.e., the second electrolyte layer, is attached to the negative electrode for assembly to obtain a composite membrane. The structural schematic diagram of the obtained membrane unit is shown in Figure 1 .

[0054] Example 2

[0055] A method for preparing a diaphragm unit:

[0056] The only difference between this embodiment and embodiment 1 is that the type of the support layer is changed: a cellulose membrane with a thickness of 15 μm is used as the membrane skeleton material, and the median value of the pore size obtained by scanning electron microscopy combined with image statistical analysis is 700 nm.

[0057] Example 3

[0058] A method for preparing a diaphragm unit:

[0059] The only difference between this embodiment and embodiment 1 is that the type of the supporting layer is changed: a 15 μm thick silica aerogel membrane, i.e., an inorganic aerogel membrane, is used as the membrane skeleton material, and the median value of the pore size is 1000 nm obtained by scanning electron microscopy combined with image statistical analysis.

[0060] Example 4

[0061] A method for preparing a diaphragm unit:

[0062] The only difference between this embodiment and embodiment 1 is that the particle size range of the first electrolyte is changed to 8 μm. At this time, the ratio of the D50 of the first electrolyte to the median pore size of the porous support is 13.33, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 1.75:1.

[0063] Example 5

[0064] A method for preparing a diaphragm unit:

[0065] The only difference between this embodiment and embodiment 1 is that the particle size range of the first electrolyte is changed to 3 μm. At this time, the ratio of the D50 of the first electrolyte to the median pore size of the porous support is 5, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 4.6:1.

[0066] Example 6

[0067] A method for preparing a diaphragm unit:

[0068] The only difference between this embodiment and embodiment 1 is that the particle size range of the second electrolyte is changed so that D50 is 300 nm.

[0069] Example 7

[0070] A method for preparing a diaphragm unit:

[0071] The difference between this embodiment and embodiment 1 is that the types of the first electrolyte and the second electrolyte are changed to lithium aluminum titanium phosphate, and the particle size range of the two remains unchanged. Lithium aluminum titanium phosphate, namely LATP, has a low intrinsic conductivity, so the battery polarization is large and the capacity is low. The corresponding performance is inferior to other embodiments, but still significantly better than the corresponding comparative example 6.

[0072] Example 8

[0073] A method for preparing a diaphragm unit:

[0074] The only difference between this embodiment and embodiment 1 is that the types of the first electrolyte and the second electrolyte are changed to poly(propylene carbonate)-coated sulfide electrolytes, and the particle size ranges of the two remain unchanged.

[0075] And, the poly(propylene carbonate) coated sulfide electrolyte used comprises a poly(propylene carbonate) coating layer and a sulfide electrolyte core, wherein the weight ratio of (propylene carbonate) to the sulfide is 0.5:100.

[0076] Example 9

[0077] A method for preparing a diaphragm unit:

[0078] The only difference between this embodiment and embodiment 1 is that in step S2, the weight ratio of the first electrolyte to the second electrolyte is changed to 68:7, so that the thickness ratio of the first electrolyte layer to the second electrolyte layer in the obtained composite electrolyte membrane is changed to 85:15, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 3.4:1.

[0079] Example 10

[0080] A method for preparing a diaphragm unit:

[0081] The only difference between this embodiment and embodiment 1 is that in step S2, the weight ratio of the first electrolyte to the second electrolyte is changed to 18:7, so that the thickness ratio of the first electrolyte layer to the second electrolyte layer in the obtained composite electrolyte membrane is changed to 60:40, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 2.4:1.

[0082] Embodiment 11

[0083] A method for preparing a diaphragm unit:

[0084] The difference between this embodiment and embodiment 1 is that the particle size range of the first electrolyte is changed to 12 μm. At this time, the ratio of the D50 of the first electrolyte to the median pore size of the porous support is 20, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 1.16:1.

[0085] Example 12

[0086] A method for preparing a diaphragm unit:

[0087] The only difference between this embodiment and embodiment 1 is that the particle size range of the first electrolyte is changed to 1.2 μm. At this time, the ratio of the D50 of the first electrolyte to the median pore size of the porous support is 2, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 11.6:1.

[0088] Embodiment 13

[0089] A method for preparing a diaphragm unit:

[0090] The only difference between this embodiment and embodiment 1 is that the particle size range of the second electrolyte is changed so that its D50 is 700 nm, ie, larger than the median value of the pore size of the porous support.

[0091] Embodiment 14

[0092] A method for preparing a diaphragm unit:

[0093] The difference between this embodiment and embodiment 1 is only in step S2.

[0094] Specifically:

[0095] According to the weight ratio of the first electrolyte: the second electrolyte = 1:4, a sulfide (Li6PS5Cl) electrolyte with a D50 of 5 μm is selected as the first electrolyte, and a binder nitrile butadiene rubber accounting for 2% of the total weight of the first electrolyte is added, and then p-xylene is used as a dispersion solvent to obtain a first suspension slurry with a solid content of 70wt%; a sulfide (Li6PS5Cl) electrolyte with a D50 of 500nm is selected as the second electrolyte, and a binder nitrile butadiene rubber accounting for 2% of the total weight of the second electrolyte is added, and then p-xylene is also used as a dispersion solvent to obtain a second suspension slurry with a solid content of 60wt%;

[0096] The first slurry is coated on one side of the membrane skeleton material, and after drying and rolling to form a first electrolyte layer with a thickness of 14 μm;

[0097] The second slurry is coated on the other side of the membrane skeleton material and soaked into the membrane skeleton material. After drying and rolling densification, it forms a porous support layer together with the non-woven fabric (the total weight of the porous support layer obtained after drying is 100%, of which the content of the second electrolyte is 95%). At the same time, a second electrolyte layer with a thickness of 6 μm is also formed on the other side of the membrane skeleton material, thereby obtaining a composite electrolyte membrane with a total thickness of 35 μm.

[0098] Steps S3 and S4 are consistent with those in Example 1.

[0099] Embodiment 15

[0100] A method for preparing a diaphragm unit:

[0101] The difference between this embodiment and embodiment 1 is only in step S2.

[0102] Specifically:

[0103] According to the weight ratio of the first electrolyte: the second electrolyte = 1:4, a sulfide (Li6PS5Cl) electrolyte with a D50 of 5 μm is selected as the first electrolyte, and a binder nitrile butadiene rubber accounting for 2% of the total weight of the first electrolyte is added, and then p-xylene is used as a dispersion solvent to obtain a first suspension slurry with a solid content of 70wt%; a halide (LiInCl6) electrolyte with a D50 of 500nm is selected as the second electrolyte, and a binder nitrile butadiene rubber accounting for 2% of the total weight of the second electrolyte is added, and then p-xylene is also used as a dispersion solvent to obtain a second suspension slurry with a solid content of 60wt%;

[0104] The first slurry is coated on one side of the membrane skeleton material, and after drying and rolling to form a first electrolyte layer with a thickness of 14 μm;

[0105] The second slurry is coated on the other side of the membrane skeleton material and soaked into the membrane skeleton material. After drying and rolling densification, it forms a porous support layer together with the non-woven fabric (the total weight of the porous support layer obtained after drying is 100%, of which the content of the second electrolyte is 85%). At the same time, a second electrolyte layer with a thickness of 6 μm is also formed on the other side of the membrane skeleton material, thereby obtaining a composite electrolyte membrane with a total thickness of 35 μm.

[0106] Steps S3 and S4 are consistent with those in Example 1.

[0107] Comparative Example 1

[0108] A method for preparing a diaphragm unit:

[0109] The only difference between this comparative example and Example 1 is that non-woven fabric is not used as the membrane skeleton material, but the first electrolyte and the second electrolyte are directly dried to form a film to obtain a homogeneous electrolyte layer with a thickness of 35 μm, which is then laminated with the positive electrode membrane and the negative electrode membrane to obtain a membrane unit.

[0110] Comparative Example 2

[0111] A method for preparing a diaphragm unit:

[0112] The only difference between this comparative example and Example 1 is that in step S2, the weight ratio of the first electrolyte to the second electrolyte is changed to 12:7, so that the thickness ratio of the first electrolyte layer to the second electrolyte layer in the obtained composite electrolyte membrane is changed to 50:50, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 2:1.

[0113] Comparative Example 3

[0114] A method for preparing a diaphragm unit:

[0115] The only difference between this comparative example and Example 1 is that in step S2, the weight ratio of the first electrolyte to the second electrolyte is changed to 1:4, so that the thickness ratio of the first electrolyte layer to the second electrolyte layer in the obtained composite electrolyte membrane is changed to 15:85, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 0.6:1.

[0116] Comparative Example 4

[0117] A method for preparing a diaphragm unit:

[0118] The only difference between this comparative example and Example 1 is that in step S2, the weight ratio of the first electrolyte to the second electrolyte is changed to 108:7, so that the thickness ratio of the first electrolyte layer to the second electrolyte layer in the obtained composite electrolyte membrane is changed to 90:10, and the ratio of the thickness of the first electrolyte layer to the D50 of the first electrolyte is changed to 3.6:1.

[0119] Comparative Example 5

[0120] A method for preparing a diaphragm unit:

[0121] The only difference between this comparative example and Example 14 is that a polyethylene terephthalate film with a non-porous structure is used to replace the non-woven fabric therein.

[0122] The battery cell sample corresponding to this comparative example exhibits insulation, and its capacity and K value are both 0, and has no application value.

[0123] Comparative Example 6

[0124] A method for preparing a diaphragm unit:

[0125] The only difference between this comparative example and Example 7 is that non-woven fabric is not used as the membrane skeleton material, but the first electrolyte and the second electrolyte are directly dried to form a film to obtain a homogeneous electrolyte layer with a thickness of 35 μm, which is then bonded to the positive electrode membrane and the negative electrode membrane to obtain a membrane unit.

[0126] Test Method

[0127] Shear strength: Tested in accordance with GB / T 1450.2-2005.

[0128] Preparation of battery cell samples and K value test: The membrane units obtained in each embodiment and comparative example were repeatedly stacked 4 times and pressurized to prepare battery cells. The obtained battery cells were respectively connected to the charge and discharge channels for activation.

[0129] The activation process used is: 0.1C constant current charging to 4.2V, then switching to constant voltage charging to 0.02C cutoff and resting for 1h, 0.1C discharge value is 2.5V, and the discharge capacity of the battery cell is recorded; rest for 1h, then charging to 4.2V with 0.1C constant current, switching to constant voltage charging to 0.02C cutoff, standing for 72h, detecting the voltage drop to calculate the K value, which represents the voltage drop of the battery cell under certain conditions, per unit time, and measures the parameters of self-discharge caused by micro-short circuit and side reaction of the battery. The smaller the K value, the lower the self-discharge rate of the battery cell and the better the stability. The corresponding battery has better storage performance and longer service life.

[0130] The above test results are shown in Table 1.

[0131] Table 1

[0132]

[0133] From the above description, it can be seen that the above-mentioned embodiments of the present invention realize the preparation of a diaphragm unit that can take into account both high shear strength and excellent electrochemical performance. After the obtained diaphragm unit is prepared into a battery cell, the corresponding battery cell exhibits excellent capacity and discharge stability.

[0134] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A diaphragm unit, characterized in that: The membrane unit comprises a negative electrode membrane (10), a composite electrolyte membrane (20) and a positive electrode membrane (30) which are stacked in sequence; The composite electrolyte membrane (20) comprises a first electrolyte layer (21), a porous support layer (22) and a second electrolyte layer (23) which are stacked in sequence, wherein the first electrolyte layer (21) is arranged in contact with the negative electrode membrane (10), and the second electrolyte layer (23) is arranged in contact with the positive electrode membrane (30); The porous support layer (22), the first electrolyte layer (21) and the second electrolyte layer (23) all include electrolytes; The thickness ratio of the first electrolyte layer (21) to the second electrolyte layer (23) is (1.5-6.0):

1.

2. The diaphragm unit according to claim 1, characterized in that: The thickness of the porous support layer (22) is 5 μm to 30 μm; The porous support layer (22) also includes a membrane skeleton material, and the median value of the pore size of the membrane skeleton material is 600nm to 1000nm; The membrane skeleton material is selected from one or more of non-woven fabrics, cellulose membranes and inorganic aerogel membranes.

3. The diaphragm unit according to claim 2, characterized in that: The first electrolyte layer (21) includes a first electrolyte, the second electrolyte layer (23) and the porous support layer (22) both include a second electrolyte, and: The ratio of D50 of the first electrolyte to the median value of the pore size is 5 to 15; The D50 of the second electrolyte is less than the median value of the pore size; Based on the total weight of the porous supporting layer (22) being 100%, the content of the second electrolyte is 50% to 98%.

4. The diaphragm unit according to claim 3, characterized in that: The ratio of the thickness of the first electrolyte layer (21) to the D50 of the first electrolyte is (2-20):

1.

5. The diaphragm unit according to claim 2, characterized in that: The first electrolyte and the second electrolyte are each independently selected from one or more of a sulfide electrolyte, a halide electrolyte, an oxyhalide electrolyte, a lithium aluminum titanium phosphate electrolyte, a lithium aluminum germanium phosphate electrolyte, a lithium lanthanum zirconium oxide electrolyte, a lithium lanthanum titanium oxide electrolyte, and an organic / inorganic composite electrolyte; The organic / inorganic composite electrolyte is a poly(propylene carbonate)-coated sulfide electrolyte, which includes a poly(propylene carbonate) coating layer and a sulfide electrolyte core, and a weight ratio of the poly(propylene carbonate) coating layer to the sulfide electrolyte core is (0.05-1):

100.

6. A method for preparing a diaphragm unit according to any one of claims 1 to 5, characterized in that: include: Step S1, providing a membrane skeleton material, wherein the membrane skeleton material has a first surface and a second surface that are arranged opposite to each other; Step S2, preparing a first electrolyte and a second electrolyte into a slurry, and applying the slurry onto the first surface of the membrane skeleton material, so that the second electrolyte in the slurry penetrates the first surface and infiltrates the membrane skeleton material to form the second electrolyte layer (23) and the porous support layer (22); the first electrolyte forms the first electrolyte layer (21) on the first surface, thereby obtaining the composite electrolyte membrane (20); Alternatively, the first electrolyte is prepared into a first slurry, and the first slurry is applied on the first surface of the membrane skeleton material to form the first electrolyte layer (21); the second electrolyte is prepared into a second slurry, and the second slurry is applied on the second surface of the membrane skeleton material, so that the second slurry infiltrates the membrane skeleton material to form the second electrolyte layer (23) and the porous support layer (22), thereby obtaining the composite electrolyte membrane (20); Step S3, preparing the negative electrode active material into the negative electrode membrane (10); preparing the positive electrode active material into the positive electrode membrane (30); Step S4, laminating the negative electrode membrane (10) with the first electrolyte layer (21), and laminating the positive electrode membrane (30) with the second electrolyte layer (23), to obtain the membrane unit.

7. The method for preparing a diaphragm unit according to claim 6, characterized in that: In the slurry, the weight ratio of the first electrolyte to the second electrolyte is (3-4):

1.

8. The method for preparing a diaphragm unit according to claim 7, characterized in that: The solid content of the slurry, the first slurry and the second slurry is independently 20 wt % to 75 wt %.

9. A battery cell, comprising a positive electrode current collector, a negative electrode current collector and a membrane unit, characterized in that: The diaphragm unit is the diaphragm unit according to any one of claims 1 to 5.

10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the battery cell according to claim 9.

Citation Information

Patent Citations

  • Method for manufacturing solid electrolyte membrane, method for manufacturing all-solid-state battery, device for manufacturing solid electrolyte membrane, and device for manufacturing all-solid-state battery

    CN114207887B

  • Full concentration gradient composite solid electrolyte membrane and its preparation method and application

    CN117558976B

  • Solid electrolyte membrane and preparation method thereof

    CN117577930A

  • Solid electrolyte membrane, battery and preparation method of solid electrolyte membrane

    CN117832596A